APPLICATION OF SWOT ANALYSIS AS A BASIS FOR FORMULATING INTERNATIONAL CLASS MARKETING STRATEGIES IN PRIVATE HIGHER EDUCATION (CASE STUDY FALETEHAN UNIVERSITY) - Fxik Ardi Pradana; Anang Ma’ruf; Yudha Tri Buana Saputra (Journal of Information Systems and Management (JISMA), 2022)
Faletehan University is a private university located in Serang, Banten has been established since 1987 which has become one of the options for residents to send their children to school. The purpose of this study is to determine the strengths, weaknesses, opportunities and threats to find out the marketing strategies implemented in schools and to analyze the appropriate marketing strategies for schools to increase the number of student. This type of research is descriptive with a quantitative approach. The analytical method used is SWOT analysis (Strenths, Weakness, Opportunity, and Threats), with the IFAS EFAS Matrix and the Grand Strategy Matrix. The results show that the right strategy is used by Faletehan University is the Turn Around strategy. Through SWOT analysis, it is known that the school's greatest strength lies in easy location access to reach schools with a score of 0.27, while the biggest weakness is that the school does not establish good relations with embassies of other countries with a score of 0.32. The school's biggest opportunity is the increasing number of international schools in Jakarta in the last 3 years, proving that the opportunity to get prospective new students is still wide open, by obtaining a score of 0.72, while the biggest threat to schools is the existence of regulations the government limits the age of foreign workers to a maximum of 60 years and a minimum of 5 years experience in the same field, obtaining a score of 0.60